Alfabetización Informacional: una vía de acceso a la información confiable (2021)
Objective: To elaborate an action plan to implement the information literacy programme (IFLA) with the participation of students of the ICT and learning environments class at the UPTC. The purpose is to access reliable digital content, analyze the diagnosis, and design workshops that allow addressing the proposed elements. Originality/support: This discussion arises from teaching in higher education. Considering that the interaction with information has mutated due to digital contexts, it is necessary for students to filter and strengthen skills that lead them a critical view of the information they access. Method: this action research work has a qualitative approach with a theoretical foundation. Strategy/ information gathering: the design, application and analysis of diagnostic instruments allowed us to understand that this university has material and intellectual resources for an ethical management of information. Conclusions: Ethics is the emerging category of this research. This category, when properly used, empowers the construction of knowledge in societies. Likewise, its strengthening depends to a great extent on the involvement of higher education teachers.